The Effect of Salts on the Liquid-Liquid Phase Equilibria of PEG600+Salt Aqueous Two-Phase Systems - Sara C. Silvério (2013)
Six new ATPSs were prepared by combining polyethylene glycol PEG600 with potassium citrate, dipotassium hydrogen phosphate, sodium formate, potassium formate, sodium sulfate, and lithium sulfate. Complete phase diagrams, including the binodal curve and three tie-lines, were determined at 23 C. The experimental data obtained for the binodal curve were successfully adjusted to the Merchuk equation, and the reliability of tie-line data was confirmed using the equations suggested by Othmer-Tobias and Bancroft. The ability of each ion to induce ATPS formation was investigated. Na+ proved to be more effective in ATPS formation than K+ and Lit For potassium salts, the order observed for the effectiveness of the anions was: HPO42- > C6H5O73- > HCO2-. Regarding the sodium salts, it was found that SO42- is clearly more effective than HCO2-. The position of the ions in the Hofmeister series and their free energy of hydration (Delta G(hyd)) were used to explain the ability of the ions to induce PEG salting-out. Furthermore, the effective excluded volume (EEV) of the salts was determined and the following order was found: Na2SO4 > K2HPO4 > Li2SO4 > K3C6H5O7 > NaCHO2 > KCHO2. Similar order was obtained when analyzing the size of the heterogeneous regions, suggesting the practical use of EEV as a comparison parameter between different ATPSs.